Removal of nitrogen by Antarctic yeast cells at low temperature - Katayama-Hirayama,Keiko; Koike,Yuko; Kaneko,Hidehiro; Kobayashi,Kikuo; Hirayama, Kimiaki (National Institute of Polar Research, 2003)
P(論文) Nitrate removal in a medium (at 5°C ) and the effect of culture temperature on the fatty acid composition were investigated using Candida sp. which was isolated from the upper layer of Lake Vanda in the McMurdo Dry Valleys, Antarctica. The strain was cultured at 5°C aerobically, on a synthetic medium containing potassium nitrate (NO_3-N, 100 mgl^<-1>) as a nitrogen source, and examined the effects of pH and chlorine on growth and NO_3-N removal in the medium. Within the pH of 3 to 7 the yeast cells exhibited a similar removal of nitrate level. The strain grew well and also removed nitrate at chlorine concentrations of 5 and 10 mgl^<-1> but did not grow at chlorine concentration of 20 mgl^<-1>. Decreasing the growth temperature induced an increase in the content of linolenic acid (18:3) in the yeast cells. departmental bulletin paper